2006
DOI: 10.4049/jimmunol.176.5.3266
|View full text |Cite
|
Sign up to set email alerts
|

Evidence to Support the Role of HLA-G5 in Allograft Acceptance through Induction of Immunosuppressive/ Regulatory T Cells

Abstract: The soluble HLA-G5 isoform encoded by intron-4 retaining spliced transcript has been previously detected in vivo in sera and grafts from transplanted patients who had significantly better graft acceptance. These findings led us to investigate the role of HLA-G5 in tolerance induction in vitro and its biological relevance in allograft acceptance in vivo. We demonstrated that engagement of Ig-like transcript-2 and Ig-like transcript-4 receptors by HLA-G5 is involved in inhibition of T cell alloproliferative resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
164
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(182 citation statements)
references
References 38 publications
11
164
0
7
Order By: Relevance
“…Since protein aggregation was previously described as a critical factor for the biological activity of HLA-G5 on immune cells, 11 here we used this protein once aggregated onto microbeads (that is, HLA-G5-beads). We showed that UT7/EPO cell proliferation was significantly reduced by increasing concentrations of HLA-G5-beads (unpaired t-test, Po0.04 for 10 000 HLA-G5-beads per cell; Po0.01 for 20 000 and 30 000 HLA-G5-beads per cell; Po0.003 for 40 000 HLA-G5-beads per cell; n ¼ 3) (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since protein aggregation was previously described as a critical factor for the biological activity of HLA-G5 on immune cells, 11 here we used this protein once aggregated onto microbeads (that is, HLA-G5-beads). We showed that UT7/EPO cell proliferation was significantly reduced by increasing concentrations of HLA-G5-beads (unpaired t-test, Po0.04 for 10 000 HLA-G5-beads per cell; Po0.01 for 20 000 and 30 000 HLA-G5-beads per cell; Po0.003 for 40 000 HLA-G5-beads per cell; n ¼ 3) (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…11 Briefly, microbeads (Ademtech, Pessac, France) were incubated first with the 5A6G7 antibody to HLA-G5 (Exbio, Prague, Czech Republic) 2 and then with either rHLA-G5-containing medium or HLA-G5-containing plasma samples.…”
Section: Hla-g5 Treatmentmentioning
confidence: 99%
“…Mientras el ligando de ILT3 en las células T aún se desconoce, hay evidencia de que ILT4 ejerce sus efectos inmunomoduladores mediante la unión a diferentes moléculas clásicas y no clásicas CMH de clase I, tales como HLA-A, HLA-B y HLA-G1 (69,70 (71,72). Estas fosfatasas citoplásmicas pueden desfosforilar los receptores inmunitarios activados que contienen dominios ITAM, conduciendo a su inactivación, lo cual resulta en una disminución en la capacidad de estímulo por parte de la célula presentadora de antígeno a la célula T, induciendo finalmente una inhibición en la respuesta de esta última (73,74).…”
Section: Papel Central De Los Receptores Ilt3 E Ilt4 En La Regulaciónunclassified
“…Thus, sHLA-G5 inhibits T cell proliferation induced by allogeneic dendritic cells without affecting their differentiation and maturation [25]. Furthermore, naïve T cells incubated with sHLA-G5 for 18 hours become anergic to subsequent antigenic stimulation and acquire regulatory properties, as demonstrated by their ability to inhibit proliferation of other T cells in an antigen non-specific fashion [26].…”
Section: Molecular and Functional Characteristics Of Shla-gmentioning
confidence: 99%